NucTools: analysis of chromatin feature occupancy profiles from high-throughput sequencing data - Vainshtein, Yevhen; Rippe, Karsten; Teif, Vladimir (BMC genomics, 2017)
Biomedical applications of high-throughput sequencing methods generate a vast amount of data in which numerous chromatin features are mapped along the genome. The results are frequently analysed by creating binary data sets that link the presence/absence of a given feature to specific genomic loci. However, the nucleosome occupancy or chromatin accessibility landscape is essentially continuous. It is currently a challenge in the field to cope with continuous distributions of deep sequencing chromatin readouts and to integrate the different types of discrete chromatin features to reveal linkages between them.